Protein clearances and renal protein selectivity in the proteinurias of pregnancy - Simanowitz, Milton David (Department of Obstetrics and Gynaecology, 2020)
Ever since the association between altJ.Jminuria and eclampsia was noted by Lever in 1843, the kidney has figured in the forefront in the search for aetiological factors. Lever, who was a contemporary of Bright at Guy's Hospital, observed the close similarity in appearance between many of his eclamptic patients and patients with Bright's disease. Examination of the urine was the logical next step. Having fould albumin in nine out of ten eclamptic patients in whom the urine had been examined, he went on to exanine the urine of fifty "normal 11 controls, and (rather surprisingly, since one would have anticipated a proportion of unrecognised preeclamptic patients amongst these) found albumin to be absent in every case. Lever recognised the "transitory nature 11 of pregnancy proteinuria and concluded that the condition differed from the permanent proteinuria of Bright's disease.In the same month of the same year (1843), Simpson made a similar observation in Edinburgh regarding proteinuria and eclampsia. Whilst also recognising that albuminuria disappeared in those patients who survived, he never theless attributed the syndrome of albuminuria and convulsions to underlying Bright's disease. This was a view that persisted for some time despite its obvious inconsistencies. Carl Braun of Vienna endorsed this concept and the chapter dealing with albuminuria and eclampsia in his "Lerbuch" was translated and run as a series of articles in the Edinburgh Medical Journal (1856 57). In this work, Braun states firmly that eclampsia is a direct result of the uraemia resulting from poorly functioning kidneys. The kidney featured prominently in many subsequent theories on aetiology but the idea of primary renal disease being the origin of the process leading to eclampsia was shortlived.